Demographics, knowledge, and attitudes toward fe supplementation for stunting prevention at public health center, Ciamis-Indonesia - Sari, Andriana; Meyleni, Reni (Pharmaciana, 2024)
Stunting has been linked to malnutrition in children from prenatal to before five years old, a condition with 24% prevalence, according to the 2021 Indonesian Nutrition Status Survey. Ciamis (West Java, Indonesia) reported 2,334 cases (3.4%) of stunting problems in 2022. The government has introduced Fe tablets to pregnant women, but this specific intervention can only be effective if accompanied by their adequate knowledge and positive perception of its usefulness, which can be influenced by their experience, education level, and sociocultural environment. This study aimed to determine the relationship between demographic characteristics and knowledge and attitudes toward Fe supplementation. This quantitative research adopted the analytical survey and cross-sectional designs and used demographics, knowledge, and attitudes questionnaires as the research instruments. Cluster sampling in the operational area of the Sadananya Public Health Center in Ciamis obtained 151 respondents. Data were analyzed using a chi-square test in SPSS. Results show that the majority of the sample size had low knowledge (118 respondents; 77.6%) and less positive attitudes (103; 67.8%) toward Fe supplementation. There was a significant relationship between age and knowledge (p=0.044), while none was observed between knowledge and education (p=0.100) and obstetric history (p=0.057). Moreover, age, education, and obstetric history were not statistically related to attitudes toward Fe supplementation (p=0.645, 0.951, 0.792). From these findings, it can be concluded that knowledge is strongly linked to age but not to education and obstetric history. Also, there is no significant relationship between attitudes toward Fe supplementation and age, education, and obstetric history.